Impact of Building Height and Volume on Cardiac Arrest Response Time. (3rd March 2016) - Conway, Anders B.; McDavid, Andrew; Emert, Jamie M.; Kudenchuk, Peter J.; Stubbs, Benjamin A.; Rea, Thomas D.; Yin, Lihua; Olsufka, Michele; McCoy, Andrew M.; Sayre, Michael R.
Abstract: Emergency medical services (EMS) care may be delayed when out-of-hospital cardiac arrest (OHCA) occurs in tall or large buildings. We hypothesized that larger building height and volume were related to a longer curb-to-defibrillator activation interval. We retrospectively evaluated 3, 065 EMS responses to OHCA in a large city between 2003–13 that occurred indoors, prior to EMS arrival, and without prior deployment of a defibrillator. The two-tiered EMS system uses automated external defibrillator-equipped basic life support firefighters followed by paramedics dispatched from a single call center. We calculated three time intervals obtained from the computerized dispatch report and time-synchronized defibrillators: initial 911 call to address curb arrival by first unit ( call-to-curb ), curb arrival to defibrillator power on ( curb-to-defib on ), and the combined call-to-defib on interval. Building height and surface area were measured with a validated program based on aerial photography. Buildings were categorized by height as short (<25 ft), medium (26–64 ft) and tall (>64 ft). Volume was categorized as small (<60, 000 ft 3 ), midsize (60, 000–1, 202, 600 ft 3 ) and large (>1, 202, 600 ft 3 ). Intervals were compared using the two-tailed Mann-Whitney test. EMS responded to 1, 673 OHCA events in short, 1, 134 in medium, and 258 in tall buildings. There was a 1.14 minute increase in median curb-to-defib on interval from 1.97 in short to 3.11 minutes in tall buildings ( p < 0.01). Taller buildings, however, had a shorter call-to-curb interval (4.73 for short vs 3.96 minutes for tall, p < 0.01), such that the difference in call-to-defib on interval was only 0.27 minutes: 6.87 for short and 7.14 for tall buildings. A similar relationship was observed for small-volume compared to large-volume building: longer curb-to-AED (1.90 vs. 3.01 minutes, p < 0.01), but shorter call-to-curb (4.87 vs. 4.05, p < 0.01); the difference in call-to-defib on was 0.18 minutes. Both taller and larger-volume buildings had longer curb-to-AED intervals but shorter 911 call-to-curb arrival intervals. As a consequence, building height and volume had a modest overall relationship with interval from call to defibrillator application. These results do not support the hypothesis that either taller or larger-volume buildings need cause poorer outcomes in urban environments.